Termite Species Distribution in Florida and UF Termite Identification Services - Thomas Chouvenc; Rudolf H. Scheffrahn; Lyle Buss (EDIS, 2022)
There are 20 termite species established in Florida, but not all of them have a pest status, and some invasive termite species affect only parts of the state. This publication highlights where each termite species is known to be established, so that Florida residents, pest control companies and UF/IFAS Extension agents can easily learn the termite risk at any given location within the state. It is a companion resource to the online termite distribution map available at https://flrec.ifas.ufl.edu/termites-in-florida/termite-distribution/. The UF/IFAS termite research team provides identification services to ensure proper treatment of infestations. In addition, as some invasive species continue to spread, there is a need to continue reporting termite samples so that various communities across Florida have access to up-to-date knowledge of what termite species have been reported in their respective areas.